DEVELOPMENT OF MODERN TECHNOLOGY FOR COTTON CLEANING MACHINES - Tokhirova Maftuna Umidjon kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation:This article presents practical and experimental research on improving the 1XK machine designed for removing fine impurities from cotton. In the improvement project, the installation angle and mechanical structure of the pegged drums were revised, and mounting the drums at a specific inclination was found to increase cleaning efficiency. In addition, the design of the machine’s mesh surface, feed rollers, and impurity hopper was optimized, simplifying the process of separating fine contaminants. Experimental results show that the improved 1XK machine ensures high cleaning efficiency and low energy consumption in cotton cleaning, thereby reducing costs and improving economic profitability.